Inclusive Islamic Education: Building Tolerance and Harmony in a Pluralistic Society in Lombok NTB - Murdianto Murdianto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This research examines the implementation of inclusive Islamic education in building tolerance and harmony in pluralistic communities in Lombok, West Nusa Tenggara. The ethnic, cultural and religious diversity that characterizes the Lombok community requires an educational approach that is able to accommodate differences while strengthening the values of togetherness. Using a qualitative research method with a phenomenological approach, this study involved participatory observation and in-depth interviews with educational figures, religious leaders and communities in three districts in Lombok. The results show that the implementation of inclusive Islamic education through curriculum integration based on local wisdom and universal Islamic values has contributed significantly to building awareness of pluralism among students. The learning model that prioritizes intercultural and interreligious dialogue has proven effective in fostering an attitude of tolerance and mutual respect. The research findings also reveal the importance of the teacher's role in transforming Islamic values that are rahmatan lil 'alamin through a contextual approach that is relevant to the reality of the plurality of Lombok society. The implications of this research provide a theoretical and practical basis for the development of an inclusive Islamic education model that is adaptive to the needs of a multicultural society.